Multiporphyrin Arrays on Cyclophosphazene Scaffolds: Synthesis and Studies - Pareek, Yogita; Ravikanth, Mangalampalli (Chemistry : a European journal, 2012)
The stable and robust cyclotriphosphazene and cyclotetraphosphazene rings were used as scaffolds to prepare hexa‐ and octaporphyrin arrays by treating N3P3Cl6 and N4P4Cl8, respectively, with 5‐(4‐hydroxyphenyl)‐10,15,20‐tri(p‐tolyl)porphyrin (N4 core) or with its thiaporphyrin analogues (N3S and N2S2 cores) in THF in the presence of Cs2CO3 under simple reaction conditions. Thiaporphyrins were examined in addition to the normal porphyrin to tune the electronic properties of the resultant arrays. Observation of the molecular ion peaks in the mass spectra confirmed the molecular structures of the arrays. 1D and 2D NMR techniques were employed to characterize the multiporphyrin arrays in detail. The 1H NMR spectra of the multiporphyrin arrays each show a systematic set of signals, indicating that the porphyrin units are arranged in a symmetrical fashion around the cyclophosphazene rings. All signals in the 1H NMR spectra were assigned with the aid of COSY and NOESY experiments. The protons of each porphyrin unit are subject to upfield and downfield shifts because of the ring‐current effects of neighboring porphyrin units. Optical, electrochemical, and fluorescence studies of the arrays indicated that the porphyrin units retain their independent ground‐ and excited‐state characteristics. CuII and NiII derivatives of hexaporphyrin and octaporphyrin arrays containing N4 porphyrin units and N3S porphyrin units were synthesized, and complete metalation of the arrays was confirmed by their mass spectra and by detailed NMR characterization of the NiII derivatives of hexa‐ and octaporphyrin arrays containing N4 porphyrin units. Electrochemical studies indicated that CuII and NiII ions present in the thiaporphyrin units of the arrays can be stabilized in the +1 oxidation state, which is not possible with arrays containing normal porphyrin units. A series of multiporphyrin and multimetalloporphyrin arrays on cyclotri‐ and cyclotetraphosphazene scaffolds were synthesized (see figure). These arrays were characterized by means of spectroscopic, photophysical, and electrochemical studies.